Phloem transdifferentiation from immature xylem cells during bark regeneration after girdling in Eucommia ulmoides Oliv - Pang, Yu (Journal of experimental botany, 2008)
Eucommia ulmoides Oliv. (Eucommiaceae), a traditional Chinese medicinal plant, was used to study phloem cell differentiation during bark regeneration after girdling on a large scale. Here it is shown that new sieve elements (SEs) appeared in the regenerated tissues before the formation of wound cambium during bark regeneration after girdling, and they could originate from the transdifferentiation of immature/differentiating axial xylem cells left on the trunk. Assays of water-cultured twigs revealed that girdling blocked sucrose transport until the formation of new SEs, and the regeneration of the functional SEs was not dependent on the substance provided by the axis system outside the girdled areas, while exogenous indole acetic acid (IAA) applied on the wound surface accelerated SE differentiation. The experiments suggest that the immature xylem cells can transdifferentiate into phloem cells under certain conditions, which means xylem and phloem cells might share some identical features at the beginning of their differentiation pathway. This study also showed that the bark regeneration system could provide a novel method for studying xylem and phloem cell differentiation